Postdural Puncture Superior Sagittal Sinus Thrombosis in a Juvenile Case of Clinically Isolated Syndrome. (19th October 2015) - Michel, Miriam; Haberlandt, Edda; Baumann, Matthias; Entenmann, Andreas; Wagner, Michaela; Rostasy, Kevin
Abstract : Background . The causes of cerebral venous thrombosis (CVT) are manifold as is its clinical presentation. Case . We report the case of a CVT following lumbar puncture and intravenous glucocorticosteroid therapy in a female adolescent with a clinically isolated syndrome and risk factors for thrombosis. Conclusion . In adolescent patients with acute inflammatory disease undergoing lumbar puncture followed by intravenous high-dose glucocorticosteroid therapy, one should be aware of the elevated risk for thrombosis. A persistent headache with change in the headache pattern and loss of a postural component might be a sign for CVT, requiring emergency imaging of the brain.